Bio-inspired effective and regenerable building cooling using tough hydrogels. (15th April 2016) - Cui, Shuang; Ahn, Chihyung; Wingert, Matthew C.; Leung, David; Cai, Shengqiang; Chen, Renkun
Highlights: Application of tough hydrogel as regenerable 'sweating skin' for building cooling. Tough gel exhibits effective evaporative cooling and extraordinary cyclability. Charging and discharging capability of the tough gel was retained after 50 cycles. Tough gel cooling could lead to substantial energy saving in buildings. Abstract: Innovative thermal regulation technologies could provide great potential for reducing energy consumption in buildings. In this work, we report, for the first time, the application of highly stretchable and tough double network hydrogels (DN-Gels) as durable and reusable 'sweating skins' for cooling buildings. These DN-Gels demonstrate outstanding cooling performance, reducing the top roof surface temperature of wooden house models by 25–30 °C for up to 7 h after only a single water hydration charge. More importantly, compared with single network hydrogels (SN-Gels) previously studied for cooling applications, these DN-Gels exhibit extraordinary toughness and cyclability due to their interpenetrated ionically and covalently cross-linked networks, as demonstrated by constant cooling performance over more than 50 cycles. This excellent cyclability is further demonstrated by the unaltered mechanical properties and charging capability of the hydrogels after many cycles, compared to fresh ones. By coating a 100 m 2 roof of a single house with tough DN-Gels, it is estimated that the annual electricity consumption needed for air conditioning can be reduced by ∼290 kW h with associated CO2 emission reductions of 160 kg. Our results suggest that bio-inspired sweat cooling, specifically using tough DN-Gel coatings, represents a promising energy-efficient technology for cooling buildings as well as other devices and systems.